Beryllium layer response to ITER-like ELM plasma pulses in QSPA-Be. (August 2017) - Klimov, N.S.; Podkovyrov, V.L.; Kupriyanov, I.B.; Linke, J.; Pitts, R.A.; Safronov, V.M.; Kovalenko, D.V.; Loewenhoff, Th.; Lungu, C.P.; Pintsuk, G.; De Temmerman, G.; Muzichenko, A.D.; et al.
Highlights: Be layers (Δ h = 1–55 µm) on W and Be were tested at the ITER ELM-like plasma loads. Be layers (Δ h = 1–55 µm) on W retain their integrity at q = 0.2 MJm −2 (Δ t = 0.5 ms). Be layer melting is the main damage processes at the heat load of 0.5 MJm −2 on W. No significant melt splashing appears in spite of higher pressure than in ITER. Thickness of Be coating corresponded to minimal erosion rate exists on Be. Abstract: Material migration in ITER is expected to move beryllium (Be) eroded from the first wall primarily to the tungsten (W) divertor region and to magnetically shadowed areas of the wall itself. This paper is concerned with experimental study of Be layer response to ELM-like plasma pulses using the new QSPA-Be plasma gun (SRC RF TRINITI). The Be layers (1 → 50 µm thick) are deposited on special castellated Be and W targets supplied by the ITER Organization using the Thermionic Vacuum Arc technique. Transient deuterium plasma pulses with duration ∼0.5 ms were selected to provide absorbed energy densities on the plasma stream axis for a 30° target inclination of 0.2 and 0.5 MJm −2, the first well below and the second near the Be melting point. This latter value is close to the prescribed maximum energy density for controlled ELMs on ITER. At 0.2 MJm −2 on W, all Be layer thicknesses tested retain their integrity up to the maximum pulse number, except at local defects (flakes, holes and cracks) and on tile edges. At 0.5 MJm −2 on W, Be layer melting and melt layer agglomeration are the main damage processes, they happen immediately in the first plasma impact. Melt layer movement was observed only near plasma facing edges. No significant melt splashing is observed in spite of high plasma pressure (higher than expected in ITER). Be layer of 10 µm thick on Be target has higher resistance to plasma irradiation than 1 and 55 µm, and retain their integrity up to the maximum pulse number at 0.2 MJm −2 . For 1 µm and 55 µm thick on Be target significant Be layer losses were observed at 0.2 MJm −2 .